Learning Style in Language Learning Classroom - Fitri Devi Enjelina Silitonga; Sri Menty Pinem; Lovita Simbolon; Laura Maloni Lingga; Erikson Saragih (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This article describes the concept of language learning styles in the classroom and the characteristics of students for each of their learning styles in language learning. Where the purpose of this study is to describe their learning styles related to learning styles for language acquisition. There are 3 types of language learning styles described by Tekavcic and Dimovski namely the visual, auditory and touch functions of a person in processing information. The three main types of learning styles are not absolute, of course. Many students learn through various senses. Certain students may be as strong in three perceptual modalities, or in two perceptual modalities from any combination. The method of data collection in this study is observation, the results of this discussion are that we observed grade 9 students of Percut Sei Tuan Middle School very less on how to apply language learning styles they are in front of the class so that it impacts learning difficulties well.